Transient Activation of Superior Prefrontal Cortex during Inhibition of Cognitive Set - Konishi, Seiki (J Neurosci, 2003)
The prefrontal cortex implements a set-shifting function that includes inhibition of a previously acquired cognitive set. The impairment of the inhibitory function results in perseverative behavior that forms one characteristic feature of frontal lobe dysfunction. Previous neuroimaging studies have revealed inhibitory mechanisms in the inferior prefrontal cortex. The present functional magnetic resonance imaging study devised “dual-match” stimuli in a set-shifting paradigm that allowed us to temporally isolate the inhibitory processes recruited during exposure to a previously acquired set. Transient activation time-locked to the isolated inhibition was revealed in the left middle frontal gyrus near the superior frontal sulcus. In a control experiment conducted after subjects had been informed and made aware of the exposure, however, the superior prefrontal activation disappeared, and prominent activation was revealed in a set of brain regions that included the left posterior inferior frontal sulcus. These double dissociation results indicate inhibitory mechanisms in the superior prefrontal cortex, alternative to the inferior prefrontal ones, that are activated depending on the subjects' strategy for inhibition of cognitive set.